1999
DOI: 10.1046/j.1468-1331.1999.640431.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between an estrogen receptor gene polymorphism and Parkinson's disease with dementia

Abstract: Parkinson's disease (PD) is a common cause of dementia in the elderly. Dementia in Alzheimer's disease (AD) and PD share common biologic and clinical features. The estrogen receptor (ER) gene is one of the susceptibility genes for AD. In order to test the hypothesis that the overlap between AD and PD may have a genetic basis, we determined ER gene polymorphisms in 13 PD patients with dementia (PDD) (age ± SD; 71.9 ± 5.5 years), 71 PD patients without dementia (PDND) (68.4 ± 7.5 years), 86 AD patients (76.8 ± 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 29 publications
3
35
1
Order By: Relevance
“…The direction of these associations is supported by a majority of significant case-control studies [8][9][10][11]37], although several prior studies have reported larger effect sizes in smaller samples. These differences may be partly explained by the populations studied, as the majority of significant findings have been found in Japanese populations [10,11,37].…”
Section: Ryan 10mentioning
confidence: 84%
See 2 more Smart Citations
“…The direction of these associations is supported by a majority of significant case-control studies [8][9][10][11]37], although several prior studies have reported larger effect sizes in smaller samples. These differences may be partly explained by the populations studied, as the majority of significant findings have been found in Japanese populations [10,11,37].…”
Section: Ryan 10mentioning
confidence: 84%
“…These differences may be partly explained by the populations studied, as the majority of significant findings have been found in Japanese populations [10,11,37]. Although these ESR1genotype frequencies are relatively similar between Caucasian and Asian populations, ethnic differences in linkage disequilibrium between these polymorphisms and other functional polymorphisms is highly likely [38].…”
Section: Ryan 10mentioning
confidence: 94%
See 1 more Smart Citation
“…Studies on animal models have shown estradiol (E2) dose dependent inhibition of clinical signs of EAE when E2 was given a week before EAE induction [18] and [19]. Also of interest, several positive association results have been found between estrogen receptor variants and other autoimmune disorders including lupus and rheumatoid arthritis [20] and [21] as well as with the Parkinson neurodegenerative disease [22]. In addition, an association has also been found between the PvuII ESR1 polymorphism and the HLA DR2 allele [15] and a recent Japanese study found an independent positive association of the ESR1 PvuII T allele with HLA-DRB1 1511 allele, an allele associated with MS development [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the frequency of specific oestrogen receptor alpha gene polymorphisms is higher in women with dementia (Isoe-Wada et al ., 1999;Mattila et al ., 2000). Moreover, the risk of Alzheimer's disease has been calculated to be seven-fold greater in individuals that are homozygous for both the apolipoprotein E allele, apoE epsilon 4, and the oestrogen receptor alpha allelle ER α PPXX (Brandi et al ., 1999;Isoe-Wada et al ., 1999).…”
Section: Does Aging Affect Human Brain Responsiveness To Sex Steroids?mentioning
confidence: 99%